Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada Bengkel Mukmin - Hidayat, Acep; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to examine the influence of compensation on employee performance at Bengkel mukmin. The compensation referred to includes basic salary, incentives, bonuses, and other benefits provided to employees. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to all employees of Bengkel mukmin. Data analysis is conducted using descriptive and inferential statistical techniques, particularly simple linear regression analysis to test the hypothesis regarding the influence of compensation on employee performance. The results of the study indicate that there is a positive and significant influence between compensation and employee performance. These findings suggest that improvements in the compensation system can enhance employee motivation and performance, which in turn positively impacts the productivity and service quality of Bengkel mukmin. The implication of this study is the importance for management to review and implement more equitable and competitive compensation policies to achieve better organizational performance.